53 Incidence of pacemeker device infection: five year data from a single centre. (28th September 2016) - Mahon, C; Cosgrave, N; McCreey, C
Abstract : Background: Infections related to pacemakers (PPM) are increasing in incidence because more devices are being implanted. Strategies for prevention including anti microbial prophylaxis and managing PPM infections vary widely. Evidence to guide practice is limited. The only published guidelines in this area until recently were from the American Heart Association in 2010. Recent joint guidelines from the British Society of anti-microbial Chemotherapy, British Heart Rhythm Society, British Cardiovascular Society, British Heart Valve Society and British Society of Echocardiography promote a standardised approach to this important and increasing clinical problem. The new guidelines recognise the paucity of data and recommend prospective collection of infection rates at 6 months, 1 and 2 years (as well as per 1000 device-years) to define the baseline incidence of PPM infection against which future data could be compared. The Irish incidence of PPM infection is unknown. Extrapolating international estimates may be inappropriate due to varying case definitions and measures of incidence. Acknowledging variable follow-up periods and definitions of infection the international literature suggests an overall incidence of infection of 0.5%–2.2% of implants. There are higher incidence of infection for ICD/CRT compared with PPM and redo procedures compared with primary implants. Method: This was a single centre retrospective study looking at the incidence of PPM infection. Ethical approval was obtained from hospital ethics committee. Hospital records were reviewed and in the case of uncertainty the patient was contacted directly. Result: Between January 2010 and December 2015 there were 439 PPM inserted. There were 203 dual chamber devices and 236 single chamber devices. There were 4 (0.9%) PPM infections requiring device removal. Three of the patients were male. All were primary implant. Three of the devices were dual chamber. Two of the patients had chronic kidney disease. One patient had diabetes. There were 6 (1.3%) cases of cellulitis within 6 weeks of insertion and treated successfully with oral flucloxacillin. In May 2012 antimicrobial prophylaxis was changed from flucloxacillin to Zinacef. No increase in infection incidence was noted. In all cases of device infection procedure time was noted to be >60 minutes. Conclusion: These findings are consistent with international figures of infection rate of 1.1%. Although the numbers are too small to make any significant conclusion it is interesting to note that prolonged procedure time, chronic kidney disease and diabetes were factors present in this group of patient, all of which are known risk factors for device infection.